2019
DOI: 10.1177/1724600819858753
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance and prognostic implication of programmed death-1 ligand 2 expression in colorectal cancer

Abstract: Purpose: The aim of this study was to evaluate the clinicopathological significance and prognostic role of programmed death-1 ligand 2 (PD-L2) expression in colorectal cancer according to intratumoral components. Methods: We used immunohistochemical analysis to investigate the impact of PD-L2 expression on clinicopathological characteristics and survival in 264 human colorectal cancer tissues. We also evaluated the correlation between PD-L2 expression and PD-L1 expression. Results: PD-L2 was expressed in 17.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These findings are intuitively understandable, considering that PD-L2 expression suppresses tumor immunity as well as PD-L1 does. However, several studies have demonstrated that both PD-L2 and PD-L1 expression are favorable prognostic indicators for gastric and colorectal cancer[ 25 , 38 ]. To date, such discrepancies have been explained by differences in scoring methods, cutoff values of immunostaining, heterogeneities of carcinoma, and any bias originating from the inclusion of an insufficient number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are intuitively understandable, considering that PD-L2 expression suppresses tumor immunity as well as PD-L1 does. However, several studies have demonstrated that both PD-L2 and PD-L1 expression are favorable prognostic indicators for gastric and colorectal cancer[ 25 , 38 ]. To date, such discrepancies have been explained by differences in scoring methods, cutoff values of immunostaining, heterogeneities of carcinoma, and any bias originating from the inclusion of an insufficient number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PD-L1 in tissue does not seem to be a good biomarker in metastatic melanoma treated with targeted therapy [ 31 ], although its expression does increase in the microenvironment after the inhibition of BRAF, both in preclinical models and in tumour biopsies [ 32 , 33 ]. To our knowledge, no prior studies have been undertaken to determine PD-L1/PD-L2 in blood and to correlate their presence with the response to treatment for metastatic melanoma, although comparable studies have been conducted regarding other tumours [ 34 , 35 , 36 ]. Some papers have described the relation between PD-L2 expression and the presence of lymphatic metastases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether PD-L2 causes the immune suppression within the TME and its molecular mechanism require further investigation in the future. The association between PD-L2 expression and survival outcome has been investigated in several malignancies, including CRC, melanoma, pancreatic cancer, and esophageal cancer 33,[38][39][40][41] ; however, discrepancies between these studies have been observed. Several studies reported that high PD-L2 expression was associated with poor patient survival, including studies in esophageal cancer 32 , pancreatic ductal adenocarcinoma 42 and colorectal cancer 38,39 , and high tumor PD-L2 expression was associated with a favorable survival outcome in melanoma 40 and colorectal cancer 41 .…”
Section: Discussionmentioning
confidence: 99%